2013
DOI: 10.1590/s0034-75902013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Ambidestralidade e desempenho socioambiental de empresas do setor eletroeletrônico

Abstract: The aim of this work was to study the relationship between ambidexterity and environmental and social performance of organizations. Defined as the ability to balance efforts between exploitation and exploration activities, respectively based on incremental and radical innovations, ambidexterity has been identified as an essential capability in creating competitive advantage. Studies on the subject have been relating superior economic performance to ambidexterity, leaving a gap in relation to other dimensions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
1
16
0
6
Order By: Relevance
“…Assuming that innovation strategies are developed in order to increase the company's economic and financial sustainability through revenue and productivity growth (KAPLAN; NORTON, 2008; MINTZBERG; AHLSTRAND; LAMPEL, 2009; PORTER, 1986; SCANDELARI; CUNHA, 2013; YOSHIKUNI; JERONIMO, 2013) and that organizational performance is related to the company's ability to use internal resources in business processes (YOSHIKUNI; ALBERTIN, 2017), as well as based on previous studies in stable economies, which found that innovation influences organizational performance (FANG;LEVINTHAL, 2009;HE;WONG, 2004;JANSEN et al, 2006;SCANDELARI;CUNHA, 2013;UOTILA et al, 2009), we propose the following hypotheses: H1: Exploratory innovation is positively associated with organizational performance H2: Exploitative innovation is positively associated with organizational performance.…”
Section: Innovation and Organizational Performancementioning
confidence: 96%
See 3 more Smart Citations
“…Assuming that innovation strategies are developed in order to increase the company's economic and financial sustainability through revenue and productivity growth (KAPLAN; NORTON, 2008; MINTZBERG; AHLSTRAND; LAMPEL, 2009; PORTER, 1986; SCANDELARI; CUNHA, 2013; YOSHIKUNI; JERONIMO, 2013) and that organizational performance is related to the company's ability to use internal resources in business processes (YOSHIKUNI; ALBERTIN, 2017), as well as based on previous studies in stable economies, which found that innovation influences organizational performance (FANG;LEVINTHAL, 2009;HE;WONG, 2004;JANSEN et al, 2006;SCANDELARI;CUNHA, 2013;UOTILA et al, 2009), we propose the following hypotheses: H1: Exploratory innovation is positively associated with organizational performance H2: Exploitative innovation is positively associated with organizational performance.…”
Section: Innovation and Organizational Performancementioning
confidence: 96%
“…Innovation can be classified as exploratory and exploitative (GUPTA;SMITH;SHALLEY, 2006;JANSEN et al, 2006;SCANDELARI;CUNHA, 2013). Seminal research regarding innovation with this approach emerged with March (1991) and later in studies concerning organizational learning, strategy and entrepreneurship (JANSEN et al, 2006).…”
Section: Theoretical Review 21 Exploratory Innovation Exploitativementioning
confidence: 99%
See 2 more Smart Citations
“…March (1991, p.71) indica que o exploration está relacionado com a "capacidade gerencial de criação, inovação, experimentação, pesquisa e descoberta". Na indústria do software, o exploration pode ser definido como a criação dos novos produtos, aplicativos, armazenamentos, plataformas e módulos de enterprise resource planning ou business inteligence, ou seja, é uma propensão ao desenvolvimento de inovações radicais (Scandelari & Cunha, 2013).…”
Section: Hipótesesunclassified